A novel computerized real effort task based on sliders - David Gill; Victoria L. Prowse (Institute for the Study of Labor (IZA), 2011)
In this note, we present a novel computerized real effort task based on moving sliders across a screen which overcomes many of the drawbacks of existing real effort tasks. The task was first developed and used by us in Gill and Prowse (American Economic Review, forthcoming). We outline the design of our slider task, describe its advantages compared to existing real effort tasks and provide a statistical analysis of the behavior of subjects undertaking the task. We believe that the task will prove valuable to researchers in designing future real effort experiments, and to this end we provide z-Tree code and guidance to assist researchers wishing to implement the slider task.
urn:nbn:de:101:1-20110629864
Keywords: C90; C91; 330; real effort task; slider task; design of laboratory experiments; learning and time effects; individual heterogeneity